Enhancing Energy Efficiency and Power Output in Synchronous Generators through Neodymium Magnet Integration - Vehicle, Zacheus Jhope (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2025)
This research investigates the impact of integrating neodymium magnets into synchronous generators on energy efficiency and performance. Neodymium magnets, known for their high magnetic flux density, strong coercivity, and excellent thermal stability, offer potential enhancements over traditional ferrite magnets. Through a combination of experimental studies, computational simulations, and analytical evaluations, this study demonstrates that synchronous generators equipped with neodymium magnets achieve an 8-12% increase in energy efficiency and a 10-15% increase in power output. The superior magnetic properties of neodymium magnets facilitate more effective energy conversion and reduce operational losses, ensuring consistent performance even under challenging conditions. However, the adoption of neodymium magnets faces several challenges, including high initial costs, environmental impacts from rare-earth element extraction, technical design adaptations, and supply chain vulnerabilities. Despite these hurdles, the significant performance benefits of neodymium magnets present a compelling case for their integration into synchronous generators, promising more efficient, reliable, and sustainable power generation systems.